Diagnostic utility of MRS values in hippocampus formation of medically intractable temporal lobe epilepsy patients in HUSM - Dharmalingam, Gyathri Devi A/P (2017)
Background: Hippocampal formation analysis by magnetic resonance imaging (MRI) and proton MR spectroscopy (1H-MRS) is useful for lateralization of seizure focus and diagnosis of medical intractable temporal lobe epilepsy (MTLE). The present study assessed the diagnostic utility of MRS, MRI, and combinatorial MRI-MRS findings from hippocampal formation of MTLE patients. Methods: A total of 14 MTLE patients and 14 control subjects were underwent MRI and MRS examination on hippocampal formation. The patients were clinically diagnosed as MTLE patients and revealed unilataralization by electroencephalogram (EEG) examination. The patient was ensured seizure free for a minimum period of 24 hours before the analyses to avoid possible effect of acute post ictal changes. Results: There were significant (p<0.05) decrement in NAA/Cr and increment in Cho/Cr in ipsilateral hippocampal formation of MTLE patients compared to that of contralateral findings and control group, separately. In the evaluation of diagnostic utility of individual MRS value for detection of epileptic focus in hippocampal formation, only NAA/Cr and NAA/Cho revealed significant moderate and fair agreements with the EEG lateralization findings, respectively. Analysis by combinatorial MRS values or MRI alone revealed fair and moderate agreement with EEG lateralization findings, respectively. Analysis using combinatorial MRS+MRI showed substantial agreement with with EEG lateralization findings. The positive andnegative percentage agreements with EEG lateralization findings were 79% and 93%, respectively. Conclusion: Combinatorial MRS+MRI analysis improved the lateralization of epileptic focus and diagnosis of MTLE.